Candida sp. as a starter culture for cocoa (Theobroma cacao L.) beans fermentation - Mahazar, Nurul Husna; Sufian, N. F.; Meor Hussin, Anis Shobirin; Hussain, Norhayati; Mathawan, Melissa; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Two cocoa bean fermentation methods (spontaneous fermentation and the use of starter culture) for 7 days fermentation were compared in terms of safety and quality fermented beans. Candida sp. was used as a starter culture in this study. The safety of the fermented cocoa beans were measured by the growth colonies of pathogenic microorganisms namely Bacillus cereus, Escherichia coli, Salmonella sp., Staphylococcus aureus, and Pseudomonas sp., on Bacillus cereus agar, eosin-methylene blue (EMB) agar, xylose lysine deoxycholate (XLD) agar, Baird-Parker agar (BPA), and Pseudomonas agar, respectively. B. cereus, E. coli and Salmonella sp. were early present in both fermentations. Candida sp.-fermentation showed detection of B. cereus at 5.34 log10 CFU/g and absence after 24 hours of fermentation while in spontaneous-fermentation B. cereus was too few to count. Moreover, the log10 E. coli number in Candida sp.-fermentation and spontaneous-fermentation were reduced from 5.72 to 3.66 and from 7.15 to 4.46 on day 1 to day 3, respectively. There were no presences of pathogenic microorganisms on day 5 and day 7 for both fermentations. In term of quality, proximate analysis of spontaneous-fermentation resulted that the content of moisture, ash, fat, crude protein, crude fibre and carbohydrate was 56.47%, 2.32%, 3.17%, 7.02%, 28.14% and 2.88%, meanwhile for the Candida sp.-fermentation was 53.96%, 2.19%, 3.44%, 8.25%, 25.46% and 6.70%, respectively. This study showed that both fermentations are considered to be safe and there is no significant difference in proximate value in fermented cocoa beans from spontaneous-fermentation and Candida sp.-fermentation.